Comparison of a Shiga Toxin Enzyme-Linked Immunosorbent Assay and Two Types of PCR for Detection of Shiga Toxin-Producing Escherichia coli in Human Stool Specimens - Pulz, Matthias (American Society for Microbiology, 2003)
Shiga toxin (Stx)-producing Escherichia coli (STEC) is a major cause of sporadic cases of disease as well as serious outbreaks worldwide. The spectrum of illnesses includes mild nonbloody diarrhea, hemorrhagic colitis, and hemolytic-uremic syndrome. STEC produces one or more Stxs, which are subdivided into two major classes, Stx1 and Stx2. The ingestion of contaminated food or water, person-to-person spread, and contact with animals are the major transmission modes. The infective dose of STEC may be less than 100 organisms. Effective prevention of infection is dependent on rapid detection of the causative bacterial pathogen. In the present study, we examined 295 stool specimens for the presence of Stx-producing E. coli by three different methods: an Stx enzyme-linked immunosorbent assay, a conventional PCR assay, and a LightCycler PCR (LC-PCR) assay protocol recently developed by our laboratory at the Institute of Medical Microbiology at Hannover Medical School. Our intent was to compare these three methods and to examine the utility of the STEC LC-PCR protocol in a clinical laboratory. The addition of a control DNA to each sample to clearly discriminate inhibited specimens from negative ones enhanced the accuracy of the LC-PCR protocol. From our results, it can be concluded that LC-PCR is a very useful tool for the rapid and safe detection of STEC in clinical samples.